Cinda Park - Williams, Justin (WritingThreeSixty, 2020)
I can hear his mother in the kitchen. Humming along to Just an Illusion on the radio. All the sounds inside are in harmony with the children singing and running outside in the court. Then she bangs a lid on a pot. It startles me, even though James is unbothered. I hear sizzling and smell the onions and garlic browning. I go to the kitchen to see what she’s making. She is starting a lovely lamb curry. I wish I could have some. I haven’t tasted anything in months.